2012
DOI: 10.2106/jbjs.k.00254
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Orthosis Design on Functional Performance

Abstract: Background: High-energy extremity trauma is common in combat. Orthotic options for patients whose lower extremities have been salvaged are limited. A custom energy-storing ankle-foot orthosis, the Intrepid Dynamic Exoskeletal Orthosis (IDEO), was created and used with high-intensity rehabilitation as part of the Return to Run clinical pathway. We hypothesized that the IDEO would improve functional performance compared with a non-custom carbon fiber orthosis (BlueRocker), a posterior leaf spring orthosis, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 26 publications
(36 reference statements)
1
72
1
Order By: Relevance
“…We did not have a control group that completed only physical therapy without the use of the IDEO for 8 weeks. A previous study at this institution found the IDEO improved patients' physical performance on specific tasks more than two other commercially available ankle-foot orthoses and no brace [18]. Given the apparent clinical success of the Return to Run clinical pathway with the IDEO in returning patients to duty [1], the limited improvements with rehabilitation alone, as demonstrated by the lack of significant improvement in the first 4 weeks of this study when the IDEO was not worn, and we believe this issue had already been addressed by our prior study [18], we believe it would have been inappropriate to randomize the patients to rehabilitation with and without the IDEO.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We did not have a control group that completed only physical therapy without the use of the IDEO for 8 weeks. A previous study at this institution found the IDEO improved patients' physical performance on specific tasks more than two other commercially available ankle-foot orthoses and no brace [18]. Given the apparent clinical success of the Return to Run clinical pathway with the IDEO in returning patients to duty [1], the limited improvements with rehabilitation alone, as demonstrated by the lack of significant improvement in the first 4 weeks of this study when the IDEO was not worn, and we believe this issue had already been addressed by our prior study [18], we believe it would have been inappropriate to randomize the patients to rehabilitation with and without the IDEO.…”
Section: Discussionmentioning
confidence: 84%
“…1). The IDEO has been shown in a small cohort of patients undergoing limb salvage to result in better functional performance and to decrease the number of patients undergoing limb salvage who were considering amputation [18]. However, this study occurred at a single time point and data on validated, patient-reported outcomes were not collected.…”
Section: Introductionmentioning
confidence: 99%
“…Use of a semi-rigid, dynamic AFO inherently reduced the ROM and power capabilities at the ankle relative to controls and compensations at more proximal joints such as the knee resulted. Although none of the stiffness conditions restored all biomechanical gait parameters to those of control subjects, self-selected walking velocity was restored and previous reports have shown greater performance benefits with the IDEO compared with commercially available designs [33]. For walking, if a range of dynamic AFO stiffnesses may be appropriately prescribed, this may reduce the burden on the orthotist to experimentally test numerous designs to find the best stiffness characteristics for individual patients.…”
Section: Hip Momentmentioning
confidence: 87%
“…Patzkowski et al [33] was the first to compare three different dynamic AFOs during performance tasks in military patients with limb salvage. These AFOs were the posterior leaf spring, Blue Rocker (Allard USA Inc, Rockaway, NJ, USA), and a new custom dynamic AFO available to wounded warriors called the Intrepid Dynamic Exoskeletal Orthosis (IDEO, patent pending #20120271214).…”
Section: Introductionmentioning
confidence: 99%
“…Patzkowski et al [105] attributes the high functional loss in limb salvage patients to muscle loss, nerve injury, and pain, and indicated the need for development of better orthoses given the high rate of delayed elective amputations. In a study of these patients using the Intrepid Dynamic Exoskeletal Orthosis (IDEO) brace (shown in Fig.…”
Section: Advances In Lower Extremity Trauma Rehabilitation: Lessons Fmentioning
confidence: 99%